PERILAKU HARIAN DAN KAWIN POKSAI KUDA (Garrulax rufifrons rufifrons) DI CIKANANGA CONSERVATION BREEDING CENTRE, SUKABUMI - Rouland Ibnu Darda; Mulyati Effendi; Dimas Satria Pratomo (Universitas Pakuan, 2016)
Poksai horse (Garrulax rufifrons rufifrons) is a bird endemic to the island of Java, the bird is only found in some mountainous regions in West Java. Distribution and number of individuals poksai horses in nature can not be known with certainty, there is still a lot of data that is unknown, such as how it behavior, why is it spreading increasingly narrows, reproductive system and others.One of the Institute of conservation in Sukabumi have started doing this to kind of breeding programs namely Cikananga Conservation Breeding Centre (CCBC), but there are still some obstacles that arise during the breeding program is running. In February until March 2014 conducted research at CCBC, against 2 pairs of poksai horses. Observations using scan sampling method, for 7 hours/day divided into two time, namely at 07.00-12.00 and 13.00-15.00 GMT.Based on the results of the daily behavior of the dominant research on bird poksai is the behavior moves (94,725%), ingestive(3.93%), silent behavior (1,295%). The activity observed in the behavior of Pre-breeding activity is approaching, probe, feeding, talking, making nests, dancing, destroying the hive. From poksai 2 pairs of horses were observed only a pair of eggs and incubate successful son. Key word: Poksai horse, the behavior activity, Pre-breeding activity, Cikananga conservation breeding centre, Sukabumi.